2009
DOI: 10.1530/rep-09-0134
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-stores in sperm: their identities and functions

Abstract: Intracellular Ca 2C stores play a central role in the regulation of cellular [Ca 2C ] i and the generation of complex [Ca 2C ] signals such as oscillations and waves. Ca 2C signalling is of particular significance in sperm cells, where it is a central regulator in many key activities (including capacitation, hyperactivation, chemotaxis and acrosome reaction) yet mature sperm lack endoplasmic reticulum and several other organelles that serve as Ca 2C stores in somatic cells. Here, we review i) the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(189 citation statements)
references
References 99 publications
(170 reference statements)
3
179
1
6
Order By: Relevance
“…The acrosome behaves as an internal store of releasable calcium (41)(42)(43)(44); efflux from this reservoir through inositol 1,4,5 triphosphate (IP 3 )-sensitive channels is required for the AR initiated by all inducers (32,33,41,45). We had previously demonstrated that Rab3A acts in the AR before the release of calcium from the intracellular store (32).…”
Section: Resultsmentioning
confidence: 99%
“…The acrosome behaves as an internal store of releasable calcium (41)(42)(43)(44); efflux from this reservoir through inositol 1,4,5 triphosphate (IP 3 )-sensitive channels is required for the AR initiated by all inducers (32,33,41,45). We had previously demonstrated that Rab3A acts in the AR before the release of calcium from the intracellular store (32).…”
Section: Resultsmentioning
confidence: 99%
“…The physiologically relevant AR changes in [Ca 2+ ] i include external and internal Ca 2+ sources (Breitbart et al 2010 ;Costello et al 2009 ;Darszon et al 2011 ;Florman et al 2008 ). At the present time three different Ca 2+ channels are thought to mediate the [Ca 2+ ] i responses associated to the AR.…”
Section: The Acrosome Reactionmentioning
confidence: 95%
“…Evidence indicates internal Ca 2+ stores (i.e., the acrosome) participate releasing Ca 2+ through the IP3 receptor, the second type of Ca 2+ channel involved in the AR, which is activated as a consequence of IP3 production during the AR Florman et al 2008 ;Mayorga et al 2007 ;Publicover et al 2007 (Costello et al 2009 ;Darszon et al 2012 ).…”
Section: The Acrosome Reactionmentioning
confidence: 99%
“…An example of this is the regulation of calcium by the cell which is clearly critical for key physiological processes, e.g., motility and acrosome reaction. Whilst our knowledge of how calcium is regulated in the cell has increased substantially, 27,28 there are still fundamental gaps, e.g., the role of the putative calcium stores in the sperm neck/midpiece region. However, decades of clinical research suggest that calcium regulation can potentially be used as a tool for identifying dysfunctional cells.…”
Section: Sperm Dysfunction-old Tests Lying Dormant?mentioning
confidence: 99%